Student Perceptions of the Creation and Reuse of Digital Educational Resources in a Community Development-Oriented Organisation - Paskevicius, Michael; Hodgkinson-Williams, Cheryl (http://jl4d.org/index.php/ejl4d/article/view/253/284, 2018)
This case study explores students’ perceptions of the creation and reuse of digital teaching and learning resources in their work as tutors as part of a volunteer community development organisation at a large South African University. Through a series of semi-structured interviews, student-tutors reflect on their use and reuse of digital educational resources, and identify the challenges they experience in curating, adapting, and reusing educational resources for use in their teaching activities. The data is analysed qualitatively within the framework of an activity system (Engeström, 1987) to surface the primary systemic tensions that student-tutors face in the reuse of resources found online as well as open educational resources (OER). This study found that student-tutors sourced and used educational materials from the Internet, largely irrespective of their licensing conditions, while also creating and remixing a substantial number of educational materials to make them suitable for use in their context. We conclude that greater awareness of the availability of OER and explicit open licencing for works sourced and created within community development organisations could enhance sharing, collaboration, and help sustain high impact resources.
Keywords: _C:Canada CAN; _C:South Africa ZAF; _C:Spain ESP; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found